Assessing how global health partnerships function: an equity-informed critical interpretive synthesis - Katrina M. Plamondon; Ben Brisbois; Leslie Dubent; Charles P. Larson (BMC, 2021)
Abstract Background Global health partnerships (GHPs) are situated in complex political and economic relationships and involve partners with different needs and interests (e.g., government agencies, non-governmental organizations, corporations, universities, professional associations, philanthropic organizations and communities). As part of a mixed methods study designed to develop an equity-sensitive tool to support more equity-centred North-South GHPs, this critical interpretive synthesis examined reported assessments of GHPs. Results We examined 30 peer-reviewed articles for power dynamics, equity and inequities, and contradictions or challenges encountered in North-South partnerships. Among articles reviewed, authors most often situated GHPs around a topical focus on research, capacity-building, clinical, or health services issues, with the 'work' of the partnership aiming to foster skills or respond to community needs. The specific features of GHPs that were assessed varied widely, with consistently-reported elements including the early phases of partnering; governance issues; the day-to-day work of partnerships; the performance, impacts and benefits of GHPs; and issues of inclusion. Articles shared a general interest in partnering processes and often touched briefly on issues of equity; but they rarely accounted for the complexity of sociopolitical and historical contexts shaping issues of equity in GHPs. Further, assessments of GHPs were often reported without inclusion of voices from all partners or named beneficiaries. GHPs were frequently portrayed as inherently beneficial for Southern partners, without attention to power dynamics and inequities (North-South, South-South). Though historical and political dynamics of the Global North and South were inconsistently examined as influential forces in GHPs, such dynamics were frequently portrayed as complex and characterized by asymmetries in power and resources. Generally, assessments of GHPs paid little attention to the macroeconomic forces in the power and resource dynamics of GHPs highlights the importance of considering the broader political. Our findings suggest that GHPs can serve to entrench both inequitable relationships and unfair distributions of power, resources, and wealth within and between countries (and partners) if inequitable power relationships are left unmitigated. Conclusions We argue that specific practices could enhance GHPs' contributions to equity, both in their processes and outcomes. Enhancing partnering practices to focus on inclusion, responsiveness to North-South and South-South inequities, and recognition of GHPs as situated in a broader (and inequitable) political economy. A relational and equity-centred approach to assessing GHPs would place social justice, humility and mutual benefits as central practices-that is, regular, routine things that partners involved in partnering do intentionally to make GHPs function well. Practicing equity in GHPs requires continuous efforts to explicitly acknowledge and examine the equity implications of all aspects of partnering.